Environmentally relevant level of perfluorooctanoic acid affect the formation of aerobic granular sludge. (15th June 2023) - Xie, Zhouyun; Zhang, Ni; Yang, Guojing; Xu, Qiuxiang; Wang, Dongbo; Tang, Li; Xia, Jingfen; Li, Ping; Li, Xiaoming
Abstract: The growing increasing occurrence of perfluorooctanoic acid (PFOA) in wastewater has raised concerns about its potential impact on the environment. Nevertheless, the impact of PFOA at environmentally relevant level on the formation of aerobic granular sludge (AGS) is still a 'black box'. This study thus aims to fill this gap by comprehensive investigation of sludge properties, reactor performance and microbial community during the formation of AGS. It was found that 0.1 mg/L PFOA delayed the formation of AGS, causing relatively lower proportion of large size AGS at the end of operation process. Interestingly, the microorganisms contribute to the reactor's tolerance to PFOA by secreting more extracellular polymeric substances (EPS) to slow or block the entry of toxic substances into the cells. During the granule maturation period, the reactor nutrient removal especially chemical oxygen demand (COD) and total nitrogen (TN) were affected by PFOA, decreasing the corresponding removal efficiencies to ∼81.2% and ∼69.8%, respectively. Microbial analysis further revealed that PFOA decreased the abundances of Plasticicumulans, Thauera, Flavobacterium and Cytophagaceae_uncultured, but it has promoted Zoogloea and Betaproteobacteria_unclassified growth, which maintained the structures and functions of AGS. The above results revealed that the intrinsic mechanism of PFOA on the macroscopic representation of sludge granulation process was revealed, and it is expected to provide theoretical insights and practical support for direct adoption of municipal or industrial wastewater containing perfluorinated compounds to cultivate AGS. Graphical abstract: Image 1 Highlights: PFOA at environmentally relevant level delayed the formation of AGS. PFOA exposure significantly increased polysaccharide and protein content in the EPS. PFOA led to a decrease of reactor nutrient removal. Microbial community of AGS changed after long-term PFOA exposure.